모발 내부 지질 함량이 모발 부피 변화 및 잔머리 프리즈에 미치는 영향 - 송상훈; Sang-hun Song; 임병택; Byung Taek Im; 황병우; Byung Woo Hwang; 주장호; Jang Ho Joo; 손성길; Seongkil Son; 강내규; Nae-gyu Kang (大韓化粧品學會誌, 2020)
모발이 부스스하게 떠서 부피가 커졌거나 정발된 모발에서 이탈한 잔머리를 프리즈 모발이라고 하는데 어떤 요인이 프리즈 현상을 일으키는지에 대해서는 알려져 있지 않다. 모발 내부 지질은 탄력, 인장강도 등 물성과 관계되는데, 프리즈에 관해서는 인종 간 연구에서 프리즈 모발이 많은 아프리칸 모발과 지질량과의 관계가 보고되어 있다. 모발 외부에 손상을 입히지 않고 모발의 내부 지질량을 조절하는 방법은 세정에 의한 소실이 유일하지만 세정횟수와 지질 소실량은 비례하지 않는다. 본 연구에서는, 다양한 컨디셔닝 폴리머와 극성이 서로 다른 오일을 사용한 샴푸 처방으로 모발을 세정하여 모발 내부 지질량을 분석하였다. 그 결과 오일의 극성도가 높을수록 지질량이 많이 보존되는 것을 확인하였다. 이 방법을 인디언 프리즈 모발에 적용하여 프리즈 정도를 평가한 결과 지질량이 적은 모발일수록 부피가 커지는 볼륨 프리즈 정도가 심하다는 것을 발견하였다. 반면에 잔머리 프리즈 모발 부피는 지질량이 많은 모발에서 더 넓게 관찰되었다. 아울러 모발 표면 마찰력은 처리한 오일에 따른 차이가 없었기 때문에 모발 프리징은 오일간 점착력에 영향을 받지 않고 모발 내 지질량의 영향을 받고 있음을 알 수 있었다. 따라서 본 연구는 안티 프리즈 기술을 구현하는데 모발 내부 지질 조절이 중요한 해법이 될 수 있음을 제시한다. A frizz hair is referred to the fly-away hairs that have become bulky or deviated from the regular hair and the cause of that is not clear known. The internal lipids are related to the physical properties of hair such as elasticity and tensile strength and interracial studies have previously conducted to relate the lipid mass and Afrikaan hair, which has a lot of frizzy hair. Although washing hair is the only way to control the hair loss without damage of hair surface, the number of washing and lipid loss are not linearly correlated. In this study, the amount of lipid hair was analyzed by washing the hair with a few different types of shampoos containing various conditioning polymers and oils of different polarities. The results confirmed that the higher the polarity of the oil, the higher the lipid content. This method was applied to Indian frizzy hair to evaluate the degree of frizziness and found that the frizzy volume was more severe for a hair with less lipids. On the other hand, the frizzy hair volume of fly-away hairs was observed more broadly for the hairs with higher lipid contents. In addition, the friction on the surface of the hair did not differ due to the oil treatment. Taken together, it was concluded that hair frizzing was affected by the amount of lipids in the hair rather than by the adhesion between the oils. Thus, this study suggests that controlling the lipid contents in hair may be an important solution in the development of hair anti-frizzy technology.